2012
DOI: 10.1603/en11112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Traps, Lures, and Repellents for Xylosandrus compactus (Coleoptera: Curculionidae) and Other Ambrosia Beetles on Coffea arabica Plantations and Acacia koa Nurseries in Hawaii

Abstract: The black twig borer, Xylosandrus compactus (Eichhoff) (Coleoptera: Curculionidae: Scolytinae), is a pest of coffee and many endemic Hawaiian plants. Traps baited with chemical attractants commonly are used to capture ambrosia beetles for purposes of monitoring, studying population dynamics, predicting outbreaks, and mass trapping to reduce damage. The objectives of this research were to optimize trapping systems for X. compactus and other ambrosia beetles such as Xylosandrus crassiusculus (Motschulsky) and Xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 30 publications
1
49
2
2
Order By: Relevance
“…These terpenes are long known as inhibitors for various species of Scolytinae [43], [44]. Our results are consistent with those of Burbano et al [45], who also found verbenone and α-pinene to have a repellent effect on the bark beetle Xylosandrus compactus (Eichhoff) that attacks coffee in Hawaii. These results reflect differences in detection thresholds to individual components in the blend of VOCs, which would determine whether a host is attractive or unattractive, confirming previous findings on the function of semiochemicals in inter-specific interactions in bark beetles.…”
Section: Discussionsupporting
confidence: 92%
“…These terpenes are long known as inhibitors for various species of Scolytinae [43], [44]. Our results are consistent with those of Burbano et al [45], who also found verbenone and α-pinene to have a repellent effect on the bark beetle Xylosandrus compactus (Eichhoff) that attacks coffee in Hawaii. These results reflect differences in detection thresholds to individual components in the blend of VOCs, which would determine whether a host is attractive or unattractive, confirming previous findings on the function of semiochemicals in inter-specific interactions in bark beetles.…”
Section: Discussionsupporting
confidence: 92%
“…Although most work to date on the chemical ecology of Xylosandrus species has occurred in nurseries with high population densities (Oliver & Mannion, 2001;Ranger et al, 2010Ranger et al, , 2011Reding et al, 2010;Burbano et al, 2012), we found that X. crassiusculus was most attracted to traps baited with both conophthorin and ethanol in hardwood forests. Although most work to date on the chemical ecology of Xylosandrus species has occurred in nurseries with high population densities (Oliver & Mannion, 2001;Ranger et al, 2010Ranger et al, , 2011Reding et al, 2010;Burbano et al, 2012), we found that X. crassiusculus was most attracted to traps baited with both conophthorin and ethanol in hardwood forests.…”
Section: Discussioncontrasting
confidence: 53%
“…However, further comparative studies should be conducted to determine whether other traps and/or attractive volatiles are more efficient for the monitoring of this species, as well as for mass trapping purposes. In this context, some studies have demonstrated the attractiveness of α‐pinene to many ambrosia beetles (Miller & Rabaglia, ) and the synergistic effect of this substance when combined with ethanol on X. compactus (Burbano et al ., ).…”
Section: Discussionmentioning
confidence: 97%